Proteome Analysis of Vacuoles Isolated from Fig (Ficus carica L.) Flesh during Fruit Development. (26th March 2022) - Kuang, Liuqing; Chen, Shangwu; Guo, Yan; Scheuring, David; Flaishman, Moshe A; Ma, Huiqin
Abstract: Fruit flesh cell vacuoles play a pivotal role in fruit growth and quality formation. In the present study, intact vacuoles were carefully released and collected from protoplasts isolated from flesh cells at five sampling times along fig fruit development. Label-free quantification and vacuole proteomic analysis identified 1, 251 proteins, 1, 137 of which were recruited as differentially abundant proteins (DAPs) by fold change ≥ 1.5, P  < 0.05. DAPs were assigned to 10 functional categories; among them, 238, 186, 109, 93 and 90 were annotated as metabolism, transport proteins, membrane fusion or vesicle trafficking, protein fate and stress response proteins, respectively. Decreased numbers of DAPs were uncovered along fruit development. The overall changing pattern of DAPs revealed two major proteome landscape conversions in fig flesh cell vacuoles: the first occurred when fruit developed from late-stage I to mid-stage II, and the second occurred when the fruit started ripening. Metabolic proteins related to glycosidase, lipid and extracellular proteins contributing to carbohydrate storage and vacuole expansion, and protein-degrading proteins determining vacuolar lytic function were revealed. Key tonoplast proteins contributing to vacuole expansion, cell growth and fruit quality formation were also identified. The revealed comprehensive changes in the vacuole proteome during flesh development were compared with our previously published vacuole proteome of grape berry. The information expands our knowledge of the vacuolar proteome and the protein basis of vacuole functional evolution during fruit development and quality formation.